Pengaruh Citra Merek, Kualitas Pelayanan dan Promosi Terhadap Keputusan Penggunaan Jasa Pada Lembaga Bimbingan Belajar Neutron Yogyakarta” (Studi Kasus Pada Siswa SMP dan SMA Lembaga Bimbingan Belajar Neutron Yogyakarta cabang Kompol Maksum Semarang) - Dessy Wulan Sari; Saryadi Saryadi; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2014)
This research is motivated by the intense competition of tutoring agency in Semarang lately, showed by the emergence of a range of tutoring agency which every agency has its own advantages. Every business wants the survival of the business to stay awake, always growing and make profit. There for, the Neutron Yogyakarta tutoring agency must figure out how and what can attract students to use tutoring services. This research specifically discusses about Neutron Yogyakarta tutoring agency Kompol Maksum Branch Semarang. Which in every year from  2010 to 2013 the number of students fickle and decreased in the last three years the target set by the company. If it is not solved it will threaten of Neutron Yogyakarta tutoring agency Kompol Maksum Branch Semarang in competing with other tutoring agencies.The purpose of the research to determine the effect of Brand Image, Services Quality and Promotions of the decision using Neutron Yogyakarta tutoring agency Kompol Maksum branch Semarang. This type of research is explanatory, Data were collected use questionnaire and interview method. This research used method of probability sampling that was Proportionate Stratified Random Sampling. The sample of respondense totaled 94 junior and high school students who use the service of Neutron Yogyakarta tutoring agency Kompol Maksum branch Semarang. This research uses qualitative analysis and quantitative analysis techniques. Qualitative analysis using validity test, reability test, correlation coefficient test, single and multiple regression analysis, determination coefficient test, signification test (t test and F test).Result of the whole test are indicate there is an influence between Brand Image on the Decision of Using Service by during T-test(7,436)> t table(1,9860) on significant standard 5%, and coefficient determination for variable Brand image(x1) was contribute 37,5% to Service Usage Decision and the residue 62,5%  was explain with another factor except variable Brand Image. There is an influence between Service Quality on the Decision of Using Service by during T-test(5,542)>t table(1,9860) on significant standard 5%, and coefficient determination for variable Service Quality(x2) was contribute 25% to Service Usage Decision and the residue 75% was explain with another factor except variable Service Quality. There is an influence between Promotion on the Decision of Using Service by during T-test(6,973)>t table(1,9860) on significant standard 5%, and coefficient determination for variable Promotion(x3) was contribute 34,6% to Service Usage Decision and the residue 65,4% explain with another factor except variable Promotion.Showed that there are 3 indepedent variables such as Brand Image, Service Quality and Promotions prove positive and significant effect on the depeden variable Service Usage Decision. Suggestion that can be delivered are Neutron should be more creative and innovative in marketing, well as in quality.